Missed dose error among nurses working at tertiary care hospitals, Karachi - Raja; Badil; Pawan Kumar; Sana Rehman; Gulsher (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Medication administration error (MAE) has been recognized as a serious health related issue that can lead to surge mortality and morbidity. In addition, it may rise hospitalization that, will increase the ratio of the patient. This study was accomplished to determine the missed dose error among nurses working at tertiary care hospitals in Karachi.METHODOLOGY: This analytical cross-sectional study was accomplished at Dr. Ruth K.M. Pfau Civil Hospital and Dow University Hospital, Karachi, for the period of six months from February to July 2018. The calculated sample was 204 nurses of both genders. Nurses having one year of working experience and licensed with Pakistan Nursing Council had been invited for the study. The participants were approached by a non-probability convenient sampling method. The adopted and validated questionnaire was utilized to gather the data. The data was entered and analyzed by using SPSS version 21.0.RESULTS: Out of 204 subjects, 106 (52%) were male. With respect to age, 168 (82.3%) of respondents had age below 35 years. The percentage of missed medication doses was reported to be 12.3%. In this study, nurses to patients ratio, and timing of medication administration were found statistically significant with missed dose errors p-value≤0.05.CONCLUSION: The study finding showed a small frequency of missed dose errors among nurses working in tertiary care public sector hospitals, Karachi. The majority of missed doses were recorded in the morning shift, and nurses who had more patients ratio.